PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN DAN SEKTOR KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KOTA LHOKSEUMAWE - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2017)
This study aims to Determine the effect of government spending Sector Education and Health Sector Against Human Development Index In the city of Lhokseumawe. Data are Obtained from BPS Kota Lhokseumawe with the time period 2002-2015. The method used for the data analysis is linear regression. Results of the study are: There Effect of Government Spending Against Health Sector Human Development Index and there Effect of Government Spending Education Sector Against Human Development Index. Based on the result, the authors recommend further research can be done by adding the data and other macroeconomic variables that satisfactory results, so as to have an influence on the Human Development Index